Cataloging principles of Paris (1961) and Frankfurt (2003) (Confluenţe Bibliologice, 2026)
Bibliographic descriptions preparation has been and remains an issue of cataloguer. The ﬁrst cataloging rules appeared in the 19th century and over the years have been revised and updated. The most important meetings with the participation of international experts in the theory and practice of the bibliographical descriptions were those of Paris (1961) and Frankfurt (2003).
Keywords: cataloging; Statement of International Cataloguing Principles